THE INFLUENCE OF SERVICE QUALITY, BRAND IMAGE, AND PRICE ON C'BEZT FRIED CHICKEN MAKALE TO GAIN CUSTOMER LOYALTY - Nonce, Novita; Rundu Padang, Helba; Batara Marewa, Jens (Universitas Islam Lamongan, 2024)
This study aims to determine the effect of service quality, brand image and price of C'Bezt Fried Chicken Makale on customer loyalty. This type of research is quantitative research. The population in this study were all the visitors of C'Bezt Fried Chicken. The sample in this study was calculated using the Slovin formula and the results obtained were 84 samples. The data analysis technique used in this study is multiple linear regression analysis test. The results of this study indicate that partially the variables of service quality, brand image and price have a positive and significant effect on customer loyalty in C'Bezt Fried Chicken Makale. Similarly, the variables of service quality, brand image and price simultaneously or together have a significant effect on customer loyalty to C'Bezt Fried Chicken Makale.